2008
DOI: 10.1124/mol.108.049056
|View full text |Cite
|
Sign up to set email alerts
|

Drug Binding to the Inactivated State Is Necessary but Not Sufficient for High-Affinity Binding to Human Ether-à-go-go-Related Gene Channels

Abstract: Drug block of the human ether-à -go-go-related gene Kϩ channel (hERG) is the most common cause of acquired long QT syndrome, a disorder of cardiac repolarization that may result in ventricular tachycardia and sudden cardiac death. We investigated the open versus inactivated state dependence of drug block by using hERG mutants N588K and N588E, which shift the voltage dependence of inactivation compared with wildtype but in which the mutated residue is remote from the drug-binding pocket in the channel pore. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
169
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(193 citation statements)
references
References 42 publications
21
169
3
Order By: Relevance
“…Together these findings strongly suggest that high-affinity blockers preferentially bind to the inactivated state of hERG1 channels. Contrary to this hypothesis was the observation that the IC 50 for block of wild-type and inactivation-deficient mutant channels is similar for some lowpotency compounds such as quinidine (Lees-Miller et al, 2000;Perrin et al, 2008), erythromycin, and perhexilin (Perrin et al, 2008). Moreover, drug potency of high-affinity ligands is not always proportionate to the extent of channel inactivation.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Together these findings strongly suggest that high-affinity blockers preferentially bind to the inactivated state of hERG1 channels. Contrary to this hypothesis was the observation that the IC 50 for block of wild-type and inactivation-deficient mutant channels is similar for some lowpotency compounds such as quinidine (Lees-Miller et al, 2000;Perrin et al, 2008), erythromycin, and perhexilin (Perrin et al, 2008). Moreover, drug potency of high-affinity ligands is not always proportionate to the extent of channel inactivation.…”
Section: Introductionmentioning
confidence: 64%
“…The most compelling evidence for this state-dependent block is the finding that most inactivationdeficient mutant channels exhibit dramatically reduced drug sensitivity (Suessbrich et al, 1997;Wang et al, 1997a;Ficker et al, 1998;Numaguchi et al, 2000;Perrin et al, 2008). However, there is not a simple correlation between point mutation-induced reduction or elimination of inactivation and the potency of hERG1 blockers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, Chen et al (48) showed that rotation of the inner helix facilitates high affinity drug binding, which is preferentially associated with the inactivated state (51). Second, here we have shown that mutations to every third or fourth residue in the entire S5 domain perturb inactivation, suggesting that the entire S5 domain experiences a change in environment during channel inactivation.…”
mentioning
confidence: 74%